The Influence of International Knowledge Structure in Indonesia's Nickel Downstream Policy - Nabillah Audia Putri Utami (CV. AFDIFAL MAJU BERKAH, 2026)
Indonesia introduced a controversial nickel downstreaming policy in 2020 despite limited technological and managerial capacities, triggering both domestic concerns and international disputes, including with the European Union at the World Trade Organization. This article examines the factors underlying the emergence of this policy, focusing on the role of the international knowledge structure. This study employs a qualitative approach using document-based analysis of secondary data from official reports, government publications, and digital sources. Through an interpretive framework, the concept of international knowledge structure is used as a sensitizing lens to analyze how global knowledge dynamics shape state behavior.The findings show that the international knowledge structure indirectly influences economic policy by generating new industrial demands through technological development and innovation. In this case, the growing global demand for electric vehicles creates opportunities for resource-rich countries like Indonesia to leverage nickel in global value chains. This article concludes that the international knowledge structure plays a significant role in shaping policy direction and provides strategic opportunities for developing countries to pursue economic upgrading. The study highlights the importance of aligning national strategies with global knowledge dynamics